PERBEDAAN PROKRASTINASI AKADEMIK ANTARA MAHASISWA YANG BERPACARAN DAN TIDAK BERPACARAN - Salamiah Sari Dewi; Laili Alfita (Faculty of Psychology, Universitas Medan Area, 2015)
This study aims to determine the difference of academic procrastination between students whoare dating and students who are not dating. The samples were students of Psychology at theUniversity of Medan Area totaling 1395 students. Measuring instruments used are academicprocrastination scale consisting of 36 items (r_tt = 0,929). In an effort to know the condition ofAcademic Procrastination, it is necessary to compare between the mean / average valueempirically with mean / average value of the hypothetical with regard to the number SB or SDof the variables being measured. SB or SD variable values Academic Procrastination totaling22.609; Dating Academic Procrastination of 20.040; No Dating Academic Procrastination of16.604. It states that students who are dating have academic procrastination higher thanstudents who are not dating have. Data analysis using techniques Anava 1 Line. Based on dataanalysis, found that the hypothesis proposed in this study received. This is attested to see thevalue or coefficient differences Anava coefficient F = 69.029 with p = 0.000, <0.010; Based onthese results, so hypothesis reads that Academic Procrastination is has difference in terms ofstudents who are dating and students who are not dating.